IMPLEMENTASI PEMBIASAAN KEGIATAN DZIKIR ALMA’TSURAT DALAM MEMBENTUK SPIRITUAL SISWA DI SEKOLAH MENENGAH PERTAMA ISLAM TERPADU DARRUL MAGHFIROH NGLIPAR - Khori Indah Hapsari; Syamsuddin; Indah Nurhidayat (Institut Islam Mamba'ul 'Ulum Surakarta, 2023)
This study aims to find out, Implementation of habituation of dhikr al-ma'tsurat activities in the spiritual formation of students at SMPIT Darrul Maghfiroh. Obstacles encountered in habituation of dhikr al-ma’tsurat activities in spiritual gathering of students at SMPOT Darrul Maghfiroh. Solutions in overcoming existing obstacles in habituating dhikr al-ma’tsurat activities at SMPIT Darrul Maghfiroh. This study used descriptive qualitative method. This research was conducted at SMPIT Darrul Maghfiroh Nglipar. The subjects in this study were students, and informants in this study were school principals, teachers of Islamic religious education and waka curriculum. Data collection was carried out by observation, interview, and documentation methods. To test the validity of the data (data validity) in this study through triangulation techniques. Data analysis used data reduction techniques, data presentation, and conclusions.The results show that 1) The implementation of habituation of al-ma’tsurat dhikr activities at SMPIT Darrul Maghfiroh Nglipar has an influence in shaping the spirituality of students as evidenced by the attitude of children who are getting used to starting and ending daily activities with do’a, forming a calm attitude in students in responding to all situations and being able to control emotions, and having maturity thinking in solving problems. 2) The obstacles faced during the application of dhikr al-ma’tsurat at SMPIT Darrul Maghfiroh are some students who cannot read the Qur’an properly and correctly, there are students who are cool themselves when carriying out dhikr. 3) The solution that is carried out in overcoming existing obstacles is to provide support as well as motivation to students who have not been able to read the Qur’an, provide a punnishmet so that children are not late in carrying out activities.